Shifting from Government Bursaries to a Loan Scheme in Higher Education: Exploring the Zambian Experience in Student Financial Aid - Masaiti, Gift; Mwelwa, Kapambwe; Mwale, Nelly (International Journal of African Higher Education, 2016)
One of the current critical issues in higher education in Africa and globally is about making student loans available in a sustainable and cost-effective manner. The argument is more complicated for Africa because of the complexities associated with loan schemes and the general austerity that African countries find themselves in. This article presents a case study and conceptualizes the scenario of shifting government bursaries to a student loan scheme in Zambia’s higher education sector. Based on student views (N=729) and international experience, the article presents student reactions to the announcement of the implementation of the loan scheme in Zambia. Other issues explored in detail include cost-effectiveness and sustainability, loan conditionalities and forms of assistance to poor students. The article also highlights, and provokes policymakers with, questions on student loan schemes based on international experience. These are related to the modalities of who bears the ultimate risks; when and how to make the recoveries; and difficulties associated with “means testing” for would-be beneficiaries. The article uses quantitative methodological perspectives, in which “descriptive statistics” and “factor analysis” are employed. The major finding is that Zambian students are not opposed to the introduction of the student loan scheme, instead they see it as a cost-effective way of assisting students from a vulnerable background. The article strongly recommends exploring in detail the situation in other countries, so that all strengths and weaknesses are identified and carefully considered, before implementing the scheme. Un des problèmes les plus importants pour l’enseignement supérieur aujourd’hui en Afrique et dans le monde est de mettre à disposition des étudiants des systèmes de prêts qui soient durables et rentables. Le débat est particulièrement compliqué en Afrique à cause de la complexité des systèmes de prêts et de l’austérité générale à laquelle sont confrontés les pays africains. Cet article présente une étude de cas : il conceptualise le changement d’un système de bourses étudiantes à un système de prêts étudiants en Zambie. Cet article s’appuie sur l’opinion des étudiants (N=729) et l’expérience internationale pour présenter la réaction des étudiants zambiens à l’annonce de la mise en place d’un système de prêts. Il explore aussi en détails les problèmes suivants : la rentabilité et la durabilité, les conditions d’accès et les aides financières disponibles pour les étudiants pauvres. En s’appuyant sur l’expérience internationale, cet article souligne par ailleurs, dans le but de provoquer les législateurs, les questionnements associés aux systèmes de prêts étudiants. Cela inclut notamment la question de la personne qui assume le risque final, de quand et comment assurer le remboursement et des difficultés associées à l’évaluation des ressources des futurs bénéficiaires. Cet article utilise une méthodologie quantitative, plus précisément il emploie des statistiques descriptives et une analyse factorielle. La principale conclusion de cet article est que les étudiants zambiens ne sont pas opposés à l’instauration d’un système de prêts étudiants : ils considèrent au contraire que c’est une manière rentable d’aider les étudiants issus de milieux vulnérables. Cet article recommande fortement d’analyser de manière détaillée la situation dans d’autres pays pour identifier et examiner attentivement les forces et les faiblesses des systèmes de prêts avant de mettre en place un tel dispositif en Zambie.